Development and validation of the systemic lupus erythematous scale amongst the system of quality of life instruments for chronic diseases QLICD-SLE (V2.0) - Yuxi Liu; Jiaqi Zhang; Honghong Xue; Mingyang Chen; Tong Xie; Chonghua Wan (Health and Quality of Life Outcomes, 2023)
Abstract Objective The present study is aimed to develop and validate a quality of life scale for systemic lupus erythematosus (SLE) patients with Chinese cultural background, QLICD-SLE (V2.0). Methods The QLICD-SLE (V2.0) was developed using a systematic approach that involved focus groups, nominal discussions, and pilot testing. A total of 428 SLE patients participated in the scale's assessment. Validity was examined through qualitative analysis, item domain correlation, multidimensional scaling, and factor analysis. Reliability was assessed using Pearson's correlation and Cronbach's alpha coefficients. To evaluate responsiveness, paired T-tests were conducted to compare pre- and post-treatment measurements with the standardised response mean (SRM) being calculated. Results Correlation and factor analyses demonstrated strong construct validity. When using SF-36 as criteria, the correlation between various domains of QLICD-SLE and SF-36 ranged from 0.55 to 0.70. Test–retest correlation coefficients exceeded 0.71, and Cronbach’s alpha coefficients for both measurements in each domain were greater than or equal to 0.75. T-test results showed that both the overall score and most facet scores within each domain showed statistically significant changes after treatment (P < 0.05), indicating reasonable responsiveness. Conclusion The QLICD-SLE (V2.0) appears to be a valid and reliable instrument for assessing the quality of life in patients with SLE.